Identify the Risk Factor in Asset Pricing: Total Skewness in Chinese Stock Markets - Yang, Mei (2009)
Prior studies on the skewness in the return distribution mainly focus on the two parts—the determinants of skewness and the implication of the skewness. The empirical researches find that expected skewness has a negative effect on the stock returns, and most studies are conducted with U.S. market data. This dissertation extends the research to the Chinese stock markets. We investigate this relation with the data of Shanghai and Shenzhen Stock Exchange markets. We conduct the Fama-MacBeth procedure, and obtain almost the similar results as Zhang (2005)’s that a negative relation between skewness variables and expected return in U.S. stock market, though the relation between the cumulative skewness measures and expected return is close to zero and positive. This difference may due to the difference observation period and the heterogeneous characters among the stock markets in different countries.